The green frogs - Heo, Yumi. (Boston : Houghton Mifflin Co., 1996)
A folktale about two green frogs who always disobey their mother, explaining why green frogs cry out whenever it rains.
Keywords: Frogs -- Folklore; Folklore -- Korea